iTRAQ-Based Comparative Proteomic Analysis of Larval Midgut From the Beet Armyworm, Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae) Challenged With the Entomopathogenic Bacteria Serratia marcescens - De Mandal, Surajit; Lin, Boda; Shi, Miaojun; Li, Yapeng; Xu, Xiaoxia; Jin, Fengliang (Frontiers in Physiology, 2020)
Entomopathogenic bacteria Serratia marcescens is widely used as an environmentally friendly biocontrol agent against various pests, including Spodoptera exigua. Understanding the immune defense mechanism of S. exigua through comparative proteomic analysis can identify the key proteins expressed in response to the microbial infection. Here, we employed the as isobaric tags for relative and absolute quantification (iTRAQ) technique to investigate the effects of S. marcescens on the proteomic expression of S. exigua. Based on the molecular functional analysis, the differentially expressed proteins (DEPs) were mainly involved in the binding process and catalytic activities. Further bioinformatics analysis revealed important DEPs that played a crucial role in innate immunity of S. exigua with recognition (C-type lectin), melanization (propanol oxidase 3, serine protease, Serine-type carboxypeptidase activity, clip domain serine protease 4), antimicrobial activity (lysozyme, lysozyme-like gloverin cecropin B), detoxification (acetyl-CoA C-acetyltransferase, 3-dehydroecdysone 3-alpha-reductase, glucuronosyltransferase, glutathione S-transferase) and others. The Quantitative real-time PCR (qRT-PCR) results further indicated the significant upregulation of the immune-related genes in Spodoptera exigua following S. marcescens infection. To the best of our knowledge, this is the first iTRAQ based study to characterize S. marcescens mediated proteomic changes in S. exigua and identified important immune-related DEPs. The results of this study will provide an essential resource for understanding the host-pathogen interactions and the development of novel microbial biopesticides against various pests.